Women’s leadership in media representation of Srikandi governor candidates - Ainun Qisthi Rosydah; Anang Sujoko (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2024)
Online media shapes the construction of women's political leadership not only through text narratives, but also through visual symbols that are an important part of political discourse. This research aims to reveal the representation of the Three Srikandi Candidates for East Java Governor 2024 in online media coverage. Using a qualitative approach with Van Leeuwen's multimodal-visual analysis method. Data were obtained through documentation and corpus data (N=30) from 21 online media, considering aspects of 5W 1H, cover both sides, time period, context, and background. The results showed that online media emphasized diversity and women's representation in politics, and displayed seriousness, professionalism, and political support for the three candidates. The findings contribute to the mainstreaming of women's political leadership through the use of superlative and visual symbols in political communication